Dissemination of Salmonella in small-scale artisanal salami production - Pereira, Juliano Gonçalves [UNESP]; Barcellos, Vinicius Cunha; Bersot, Luciano dos Santos (My University, 2019)
The aim of this study was to evaluate the dissemination of Salmonella in small-scale traditional salami production. Six different points of salami processing plant were selected and 20 samples of differents batchs were collected for the microbiological analyzes, totaling 120 samples. All samples were submitted to coliforms 35°C and 45°C counts by MPN and Salmonella detection, except for condiments, where only the presence of the pathogen was investigated. In addition, in the samples collected after smoking the pH was measured. During the salami production, the coliform counts decreased and Salmonella was isolated at all points in the flow chart with the exception of the carcass. The point where there was the high contamination was after healing (35%). Samples of condiments and salami after inlay presented 20% positivity and ground meat and final product presented 10% and 5%, respectively. It was verified that there was the dissemination of the pathogen during the production of salami and this fact occurred mainly due to failures in the food processing besides inadequate procedures of hygiene used during the production operations, being this fundamental step to obtain foods with microbiological quality and which do not pose risks of pathogen transmission.

O objetivo deste estudo foi avaliar a disseminação de Salmonella no processamento de salame artesanal. Foram selecionados seis diferentes pontos do fluxograma de produção de uma planta de processamento de pequeno porte e coletadas 20 amostras de diferentes lotes para a realização das análises microbiológicas, totalizando 120 amostras. Todas as amostras foram submetidas à pesquisa de Salmonella e NMP de coliformes a 35°C e 45°C, com exceção dos condimentos, onde foi pesquisada apenas a presença do patógeno. Além disso, nas amostras coletadas após a defumação, foi aferido o pH. Durante o processo de produção, a contaminação por coliformes decresceu e Salmonella foi isolada em todos os pontos do fluxograma, com exceção da carcaça. O ponto onde houve maior número de amostras positivas foi após a cura (35%). Amostras de condimentos e salames após o embutimento apresentaram 20% de positividade e a carne logo após a moagem e o produto final apresentaram 10% e 5%, respectivamente. Verificou-se que houve a disseminação do patógeno durante a produção de salame e este fato ocorreu principalmente por falhas no processamento do alimento além de procedimentos inadequados de higienização utilizados durante as operações de produção, sendo esta etapa fundamental para a obtenção de alimentos com qualidade microbiológica e que não ofereçam riscos de veiculação de patógenos.
Disseminação de Salmonella no processamento industrial em pequena escala de salame artesanal
Keywords: Contamination; Contaminação; Embutidos; Pathogens; Patógenos; Sausages